Yachaq and the evil of puquio: cosmopoetics of springs in the Andean community of Pairaca (Revista de Crítica Literaria Latinoamericana, 2025)
This article proposes a cosmopoetic interpretation of an oral story about the “mal de puquio” collected by the author in the community of Pairaca. For this purpose, in addition to defining cosmopoetics, a research and interpretation methodology is proposed that can be given from within the rationality of Andean stories. As it will be shown, the story collected makes it possible to make an analysis that will allow us to account for the affective relationship that the Pairaca community members establish with the beings of the territory, which they consider alive and with dialogic capacity.
Keywords: puquio; yachaq; Andean cosmopoetics; Pairaca; orality